1981
DOI: 10.1016/0002-9416(81)90264-5
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic cooperation

Abstract: The purpose of the present article was to provide a reasonably coherent picture of the concept as well as the prediction of the misunderstood phenomenon of orthodontic cooperation. A sample of seventy orthodontic patients was studied. A double-blind quasi-experimental research design was performed. Psychological instruments were used in order to measure achievement, affiliation, and attribution motivation. The following dependent variables were recorded: headgear wear, elastic wear, appliance maintenance, nonb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
5

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 7 publications
2
27
0
5
Order By: Relevance
“…A more external locus of control as shown by higher SILOC scores was associated with higher dental neglect, caries, and plaque and gingivitis prevalence as well as with a tendency to postpone needed dental treatment. Previous research has shown that an external locus of control was associated with poorer oral health indicators [11,13,14] well as poorer dental attendance [17,29,30], which were in agreement with the findings of our study. These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past.…”
Section: Discussionsupporting
confidence: 93%
“…A more external locus of control as shown by higher SILOC scores was associated with higher dental neglect, caries, and plaque and gingivitis prevalence as well as with a tendency to postpone needed dental treatment. Previous research has shown that an external locus of control was associated with poorer oral health indicators [11,13,14] well as poorer dental attendance [17,29,30], which were in agreement with the findings of our study. These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past.…”
Section: Discussionsupporting
confidence: 93%
“…17,18,27 Among the various psychological inventories, the LOC scale has proved particularly useful, especially in the prediction of healthenhancing behavior. [3][4][5][6][7][8] This study was inspired by a previous report that concluded that LOC information might be useful to enhance patient compliance in orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a patient who is a good brusher is not necessarily a good headgear wearer, and vice versa. 18 Although measurement of compliance has been attempted with reliable systems such as built-in timing devices in various appliances, [29][30][31][32] these could only measure appliance wear time objectively. Some research has focused on the effect of sex differences and ages on compliance with appliance wear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muitas especulações foram feitas sobre o perfil psicológico de um paciente cooperador 4,50 , quais fatores teriam influência sobre seu comportamento e como seria possível mensurar por meio de testes psicológicos 17,18,20,21,37,49 estas tendências de conduta. Allan e Hodgson 4 consideraram que o perfil de um paciente cooperador incluiria quase sempre qualidades como ser amigável, responsável e atencioso, além de otimistas, obedientes, sociáveis e com bom desempenho escolar 9 .…”
Section: Revisão De Literaturaunclassified